High-fraction brookite films from amorphous precursors. Issue 1 (December 2017) - Haggerty, James; Schelhas, Laura; Kitchaev, Daniil; Mangum, John; Garten, Lauren; Sun, Wenhao; Stone, Kevin; Perkins, John; Toney, Michael; Ceder, Gerbrand; Ginley, David; Gorman, Brian; et al.
Abstract Structure-specific synthesis processes are of key importance to the growth of polymorphic functional compounds such as TiO2, where material properties strongly depend on structure as well as chemistry. The robust growth of the brookite polymorph of TiO2, a promising photocatalyst, has been difficult in both powder and thin-film forms due to the disparity of reported synthesis techniques, their highly specific nature, and lack of mechanistic understanding. In this work, we report the growth of high-fraction (~95%) brookite thin films prepared by annealing amorphous titania precursor films deposited by pulsed laser deposition. We characterize the crystallization process, eliminating the previously suggested roles of substrate templating and Na helper ions in driving brookite formation. Instead, we link phase selection directly to film thickness, offering a novel, generalizable route to brookite growth that does not rely on the presence of extraneous elements or particular lattice-matched substrates. In addition to providing a new synthesis route to brookite thin films, our results take a step towards resolving the problem of phase selection in TiO2 growth, contributing to the further development of this promising functional material.